(untitled) (Journal of Mechanical Engineering, 2009)
In this study, tribological properties of thermally sprayed WC-Cr-Ni cermet coating were investigated experimentally under lubricated rolling with sliding contact conditions. Hi-HVOF sprayed WC cermet coatings were deposited onto the axially ground, blasted and circumferentially ground roller specimens made of carburized hardened steel. Under extreme operating conditions such as contact pressure PH = 1.4 GPa, slip ratio s = - 28.0% and mating surface roughness Rmax = 6.0 Âµm, the effects of substrate surface finish on the tribological properties of the cermet coating were examined. It was found that cermet coating showed a long life and durability was not influenced by the substrate surface finish. It was also found that coefficient of friction, oil film formation, surface temperature and oil film thickness were not much influenced by the substrate surface finish. On the other hand, surface hardness, surface roughness and coating material loss were significantly influenced depending on the substrate surface finish. Keywords: Substrate surface finish, Tribological properties, WC-Cr-Ni cermet doi:10.3329/jme.v39i1.1828 Journal of Mechanical Engineering, vol. ME39, No. 1, June 2008 13-17